2015
DOI: 10.1007/s00003-014-0927-3
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of glyphosate findings in human urine samples and comparison with the exposure of operators and consumers

Abstract: For active substances in plant protection products (PPP) with well defined urinary elimination, no potential for accumulation and virtually no metabolism, measuring of urine levels could be a powerful tool for human biomonitoring. Such data may provide reliable estimates of actual internal human exposure that can be compared to appropriate reference values, such as the 'acceptable daily intake (ADI)' or the 'acceptable operator exposure level (AOEL)'. Traces of the active compound glyphosate were found in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 10 publications
(17 reference statements)
4
125
1
2
Order By: Relevance
“…Critical gaps in the re-registration of glyphosate, including the EU re-registration process itself, have been addressed (European Parliament Council, 2002;Myers et al, 2016), particularly those considered more pressing by recent scientific findings. These include: (a) increasing exposures of EU citizens to glyphosate residues, supported by human and environmental biomonitoring data in limited number (Curwin et al, 2007;Mesnage et al, 2012;Krüger et al, 2014;Niemann et al, 2015;Connolly et al, 2017;Conrad et al, 2017;Mills et al, 2017;Vandenberg et al, 2017), but identifying a clearly rising trend; (b) carcinogenicity classification by IARC, evidence of linkages of glyphosate or its formulated products to non-Hodgkin's lymphoma (Hardell et al, 2002;De Roos et al, 2003Eriksson et al, 2008;Schinasi and Leon, 2014;Mesnage et al, 2015b), and effective dose levels indicated in rodent oncogenicity studies being 1-2 orders of magnitude lower when formulated glyphosate-based herbicides were used compared to those obtained with the pure active ingredient; (c) evidence of contributions to fatal chronic kidney disease by glyphosate in areas with heavy metals in water (Jayasumana et al, 2014(Jayasumana et al, , 2015 and the finding of nonalcoholic fatty liver disease upon exposure to a glyphosatebased herbicide (Roundup R ) (Mesnage et al, 2017b), coupled with the powerful animal metabolism data embedded within the re-registration document appendices (showing glyphosate and AMPA levels higher in kidney than in liver, and much higher than in muscle tissue); as well as (d) problems (e.g., risk assessment studies for regulatory purposes of re-registration of glyphosate being carried out with pure glyphosate) arising from the dual character of pesticide registration in the EU with active ingredients authorized at EU and formulated products at MS level (Klátyik et al, 2017a). In light of these findings, earlier risk assessment statements (Williams et al, 2000) are untenable for both hazard and exposure levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical gaps in the re-registration of glyphosate, including the EU re-registration process itself, have been addressed (European Parliament Council, 2002;Myers et al, 2016), particularly those considered more pressing by recent scientific findings. These include: (a) increasing exposures of EU citizens to glyphosate residues, supported by human and environmental biomonitoring data in limited number (Curwin et al, 2007;Mesnage et al, 2012;Krüger et al, 2014;Niemann et al, 2015;Connolly et al, 2017;Conrad et al, 2017;Mills et al, 2017;Vandenberg et al, 2017), but identifying a clearly rising trend; (b) carcinogenicity classification by IARC, evidence of linkages of glyphosate or its formulated products to non-Hodgkin's lymphoma (Hardell et al, 2002;De Roos et al, 2003Eriksson et al, 2008;Schinasi and Leon, 2014;Mesnage et al, 2015b), and effective dose levels indicated in rodent oncogenicity studies being 1-2 orders of magnitude lower when formulated glyphosate-based herbicides were used compared to those obtained with the pure active ingredient; (c) evidence of contributions to fatal chronic kidney disease by glyphosate in areas with heavy metals in water (Jayasumana et al, 2014(Jayasumana et al, , 2015 and the finding of nonalcoholic fatty liver disease upon exposure to a glyphosatebased herbicide (Roundup R ) (Mesnage et al, 2017b), coupled with the powerful animal metabolism data embedded within the re-registration document appendices (showing glyphosate and AMPA levels higher in kidney than in liver, and much higher than in muscle tissue); as well as (d) problems (e.g., risk assessment studies for regulatory purposes of re-registration of glyphosate being carried out with pure glyphosate) arising from the dual character of pesticide registration in the EU with active ingredients authorized at EU and formulated products at MS level (Klátyik et al, 2017a). In light of these findings, earlier risk assessment statements (Williams et al, 2000) are untenable for both hazard and exposure levels.…”
Section: Resultsmentioning
confidence: 99%
“…Within these studies, one report compared glyphosate levels in the urine of humans and livestock, and found over one order of magnitude higher levels in the latter (Krüger et al, 2014). A survey of the human biomonitoring studies argued that the results posed no health concerns as corresponding exposures were estimated to be magnitudes below the ADI or Acceptable Operator Exposure Level values, but conceded characteristic differences between exposure levels in Europe and North America with substantially higher maximum levels in the latter region (Niemann et al, 2015), levels being 0.65-5 ng/ml in Europe and 18-233 in the US. A systematic study carried out in Southern California found that the mean glyphosate and AMPA levels in human urine increased between 1993 and 2016, and reached 0.449 and 0.401 ng/ml, respectively (Mills et al, 2017).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…But should this raise any concerns? As Niemann [33] pointed out, this increase would account for less than 0.2% of the proposed reference dose, which is no point of concern. Unfortunately, our society is influenced by these statements, and without critical literacy, this opinion will lead to decision making based on fear, possibly resulting in the banning of GMOs with resistance to glyphosate.…”
Section: Critical Literacy In Current Agriculture Debatesmentioning
confidence: 99%
“…Unfortunately, many of the readers will not use their critical literacy abilities. As discussed, Niemann [33] pointed out that the increase in urine glyphosate is irrelevant. Furthermore, the comparison is extremely biased.…”
Section: Critical Literacy In Current Agriculture Debatesmentioning
confidence: 99%
“…Metabolism can produce problems if the breakdown products are more toxic or reactive, and some chemicals can persist in the body -but what about glyphosate? Absorbed glyphosate is not readily or highly metabolized in humans, is not fat soluble, and does not accumulate in the body over time, but rather is excreted in the urine either unchanged or with its predominant metabolite, AMPA [38,39].…”
Section: A Word To the Public In Egypt And Other Developing Countriesmentioning
confidence: 99%